Skin Picking in Atopic Dermatitis and Psoriasis Patients: A Single-centre Cross-sectional Study in China - Yanjiao Ju; Mufeng Li; Xueyan Lu; Cheng Zhao; Chunlei Zhang; Zhiqiang Xie (Medical Journals Sweden, 2022)
Abstract is missing (Short communication)